Settling Scores: Best Practice for the Maintenance of Sheet Music - de Rege, Risa (CAML Review / Revue de l'ACBM, 2023)
While music libraries fundamentally face the same preservation concerns as any other library, their collections face unique problems. Sheet music is heavily used in distinct ways, and comes in a wide variety of sizes, shapes, and formats, all of which lead to maintenance issues that apply specifically to these materials. Arguing that genre and use inform the formats and damage we see in sheet music, this paper systematically explores the different features of scores, including bindings, sizes, and uses. I discuss the major preservation issues faced by circulating, printed music collections and suggest possible solutions.